2015
DOI: 10.3201/eid2112.141229
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H6N1) Virus in Dogs, Taiwan

Abstract: We determined the prevalence of influenza A virus in dogs in Taiwan and isolated A/canine/Taiwan/E01/2014. Molecular analysis indicated that this isolate was closely related to influenza A(H6N1) viruses circulating in Taiwan and harbored the E627K substitution in the polymerase basic 2 protein, which indicated its ability to replicate in mammalian species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…For example, in southern and eastern China, H6N6 AIVs were isolated from swine with clinical signs, 11, 12 and in Taiwan, an H6N1 virus was isolated from a dog. 13 Recent seroprevalence research showed seropositivity for H6 viruses among occupational exposure workers in 19 provinces of China, 14 and veterinarians exposed to birds showed H6-specific antibody was significantly elevated in United States. 15 In May 2013, an H6N1 virus was isolated in Taiwan from a 20-year-old woman with symptoms including fever, cough, headache and muscle ache.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in southern and eastern China, H6N6 AIVs were isolated from swine with clinical signs, 11, 12 and in Taiwan, an H6N1 virus was isolated from a dog. 13 Recent seroprevalence research showed seropositivity for H6 viruses among occupational exposure workers in 19 provinces of China, 14 and veterinarians exposed to birds showed H6-specific antibody was significantly elevated in United States. 15 In May 2013, an H6N1 virus was isolated in Taiwan from a 20-year-old woman with symptoms including fever, cough, headache and muscle ache.…”
Section: Introductionmentioning
confidence: 99%
“…Although outbreaks of Influenza A virus in dogs and horse populations worldwide have been reported, canine (CIV) and equine influenza virus (EIV) had not been detected in Mexico until now. However, the presence of the virus in pets had already been reported in other parts of the world increasing its incidence in domestic animals (Payungporn et al, 2008;Song et al, 2008;Lee et al, 2010;Lin et al, 2015). In this study, 58 nasal fluid, 5 lung necropsies and 5 conjunctival swabs samples from pet dogs with acute respiratory symptoms were used to detect Influenza A virus through matrix gene amplification with the WHO recommended primers.…”
Section: Discussionmentioning
confidence: 98%
“…Sustained canine influenza virus (CIV) infections are more often observed where there are dense populations of dogs, such as animal shelters, races, and dog farming (Voorhees et al, 2018). In the last five years, there have been several reports of canine species infected with IAVs of at least six different subtypes (H1N1, H3N2, H3N8, H5N1, H6N1, H9N2) (Jang et al, 2017;Sun et al, 2013;Songserm et al, 2006;Lin et al, 2015). In recent years, more serious influenza infections in dogs with AIVs have been observed, some of which have caused sustained IAV transmission of virus among dogs (Giese et al, 2008;Song et al, 2008).…”
Section: Canine Influenzamentioning
confidence: 99%